Association between postpartum depression and the practice of exclusive breastfeeding in the first three months of life - Catarine S. Silva; Marilia C. Lima; Leopoldina A.S. Sequeira‐de‐Andrade; Juliana S. Oliveira; Jailma S. Monteiro; Niedja M.S. Lima; Rijane M.A.B. Santos; Pedro I.C. Lira (Brazilian Society of Pediatrics, 2017)
Objective: To investigate the association between postpartum depression and the occurrence of exclusive breastfeeding. Method: This is a cross‐sectional study conducted in the states of the Northeast region, during the vaccination campaign in 2010. The sample consisted of 2583 mother-child pairs, with children aged from 15 days to 3 months. The Edinburgh Postnatal Depression Scale was used to screen for postpartum depression. The outcome was lack of exclusive breastfeeding, defined as the occurrence of this practice in the 24 h preceding the interview. Postpartum depression was the explanatory variable of interest and the covariates were: socioeconomic and demographic conditions; maternal health care; prenatal, delivery, and postnatal care; and the child's biological factors. Multivariate logistic regression analysis was conducted to control for possible confounding factors. Results: Exclusive breastfeeding was observed in 50.8% of the infants and 11.8% of women had symptoms of postpartum depression. In the multivariate logistic regression analysis, a higher chance of exclusive breastfeeding absence was found among mothers with symptoms of postpartum depression (OR = 1.67; p < 0.001), among younger subjects (OR = 1.89; p < 0.001), those who reported receiving benefits from the Bolsa Família Program (OR = 1.25; p = 0.016), and those started antenatal care later during pregnancy (OR = 2.14; p = 0.032). Conclusions: Postpartum depression contributed to reducing the practice of exclusive breastfeeding. Therefore, this disorder should be included in the prenatal and early postpartum support guidelines for breastfeeding, especially in low socioeconomic status women.